2016
DOI: 10.1080/13607863.2016.1211621
|View full text |Cite
|
Sign up to set email alerts
|

Psychological well-being over time among informal caregivers caring for persons with dementia living at home

Abstract: Informal caregiving for PwDs living at home is a complex task. Our study shows that caregivers' psychological well-being was associated with, among other things, less caregiver burden and higher QoL. Professionals should be aware of PwD neuropsychiatric symptoms that might affect caregivers' psychological well-being, and provide proper care and treatment for caregivers and PwDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 41 publications
1
40
0
3
Order By: Relevance
“…38 Pior saúde do alvo de cuidados também foi associada com menor nível de felicidade do cuidador. 39 Com relação à associação entre aspectos psicológicos da qualidade de vida dos cuidadores e dependência em atividades da vida diária (AVD), Lethin et al 25 identificaram que os cuidadores com maior bem-estar psicológico cuidavam de idosos com mais comorbidades, menor comprometimento cognitivo e menor dependência em AVD. Lu et al 33 verificaram que a dependência do idoso em AVD também foi associada com a satisfação com a vida do cuidador.…”
Section: Condições De Saúde Do Alvo De Cuidadosunclassified
See 2 more Smart Citations
“…38 Pior saúde do alvo de cuidados também foi associada com menor nível de felicidade do cuidador. 39 Com relação à associação entre aspectos psicológicos da qualidade de vida dos cuidadores e dependência em atividades da vida diária (AVD), Lethin et al 25 identificaram que os cuidadores com maior bem-estar psicológico cuidavam de idosos com mais comorbidades, menor comprometimento cognitivo e menor dependência em AVD. Lu et al 33 verificaram que a dependência do idoso em AVD também foi associada com a satisfação com a vida do cuidador.…”
Section: Condições De Saúde Do Alvo De Cuidadosunclassified
“…44 E os menores com maior felicidade. 25,26,43 A sobrecarga também foi negativamente associada com a dimensão psicológica da qualidade de vida. 37,38 Os estudos corroboram a importância de se avaliar e intervir na sobrecarga percebida.…”
Section: Sobrecarga Do Cuidadorunclassified
See 1 more Smart Citation
“…A previous study found that higher psychological well-being is related to reduced caregiver burden and a higher quality of life among caregivers of persons with dementia living at home. 50 Thus, the underlying construct of the COPE Index may be related to the dementia caregivers' perception of caregiver burden. As none of the criteria used were burden-specific instruments, this assumption should be addressed in detail in future studies.…”
Section: Criterion Validitymentioning
confidence: 99%
“…Among caregivers to older adults the most studied population has been caregivers to cognitively impaired care recipients, although other conditions have attracted increasing interest, such as cancer [47][48][49], stroke [2,45,[50][51][52][53][54], home-based dialysis [55], heart failure [56], multiple sclerosis [57][58][59], dementia [60], and amyotrophic lateral sclerosis (ALS) [61]. Caregiving research has also emerged from new geographical areas, including Japan [36,62,63], Taiwan [64], China [48,55], and so-called developing countries [65][66][67].…”
Section: The Current State Of Research On Caregivingmentioning
confidence: 99%